Data from: The thick-billed murre (Uria lomvia) in Northwest Greenland (Avanersuaq) relies on Arctic cod (Boreogadus saida) in a changing climate ... - Falk, Knud; Merkel, Flemming; Bergsma, Myrthe; Johansen, Kasper; Kampp, Kaj; Labansen, Aili; Mosbech, Anders; Oshima, Maasannguaq; Bouchard, Caroline (Dryad, 2025)
Considering seabirds as indicators of environmental change, we compared thick-billed murre (Uria lomvia) adult and chick diet in the North Water polynya region (NOW), NW Greenland, during 1997 and 2023. In the adult murre diet, fish accounted for 86% and 42% of food items by number and 90% and 99% by wet mass (WM) in 1997 and 2023, respectively. Arctic cod (Boreogadus saida) was the most important prey, contributing 90% and 99% of WM in 1997 and 2023, respectively. In 1997 the murres ate mostly small 1-year old cod but in 2023 they mainly took larger 2- and 3-year old Arctic cod. In the chick diet, gadids contributed 71% and 86% of prey items brought to the chicks in 1997 and 2023, respectively, supplemented by sculpins and eelpouts in 1997. Capelin (Mallotus villosus) increasingly occur in the area but did not appear in the murre diet. The study highlights a consistent reliance on Arctic cod, although with differences between sampling years in size of ingested specimens. We recommend continued monitoring of ... : # The thick-billed murre (Uria lomvia) in Northwest Greenland (Avanersuaq) relies on Arctic cod (Boreogadus saida) in a changing climate [https://doi.org/10.5061/dryad.2jm63xt05](https://doi.org/10.5061/dryad.2jm63xt05) ## Description of the data and file structure Stomach contents of thick-billed murres (*Uria lomvia*) collected in Northwest Greenland – 40 birds from 1997 and 40 from 2023 – were analyzed according to the methods described in the journal article. See sampling locations in Figure 1 of the journal article. ### Files and variables #### File: Prey_items_identified_in_NW_Greenland_Thick-billed_Murre_stomachs_1997-2023.csv Description: Identification of stomach contents of Thick-billed Murres (*Uria lomvia*) in Northwest Greenland 1997 and 2023 ##### Variables * Raw data for journal article published in Arctic Science, data pooled for proventriculos and gizzard: Coll_Date Collection date Bird_ID Unique identifier of each sampled bird Sex Sex of the collected murre ItemType Type of item - ...